2020
DOI: 10.1111/ajt.15851
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization using imlifidase and EndoS enables chimerism induction in allosensitized recipient mice

Abstract: Mixed hematopoietic chimerism induction as a way to foster tolerance to donor organs in recipients who have been sensitized to donor antigens is challenging. Donor‐specific antibodies (DSA) are a dominant barrier toward successful donor bone marrow engraftment. Although desensitization methods are routinely used in recipients with allosensitization for allogeneic bone marrow transplantation, engraftment is frequently unsuccessful. To overcome the barrier of prior sensitization we tested enzymatic desensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Along with EndoS, it has further potential use in the deactivation of pathogenic antibodies in autoimmune disorders 13 19 , deactivation of neutralising antibodies for in vivo gene therapy 20 , and for the potentiation of therapeutic antibodies by deactivation of competing serum IgG 21 , 22 . Imlifidase has also been used in combination with EndoS for inactivation of donor-specific antibodies in murine allogeneic bone marrow transplantation 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Along with EndoS, it has further potential use in the deactivation of pathogenic antibodies in autoimmune disorders 13 19 , deactivation of neutralising antibodies for in vivo gene therapy 20 , and for the potentiation of therapeutic antibodies by deactivation of competing serum IgG 21 , 22 . Imlifidase has also been used in combination with EndoS for inactivation of donor-specific antibodies in murine allogeneic bone marrow transplantation 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To further reduce the titer and inhibit the effector functions of residual DSA, Anderson et al. ( 87 ) demonstrated that a combination of imlifidase and EndoS can be used to inactivate DSA and inhibit DSA-mediated killing of donor BM cells in allogeneic BM transplantation. Further studies are needed to confirm whether enzyme-mediated DSA blocking prevents antibody rebound.…”
Section: The Soilmentioning
confidence: 99%
“…Along with EndoS, it has further potential use in the deactivation of pathogenic antibodies in autoimmune disorders 13− 19 , deactivation of neutralising antibodies for in vivo gene therapy 20 , and for the potentiation of therapeutic antibodies by deactivation of competing serum IgG 21,22 . Imli dase has also been used in combination with EndoS for inactivation of donor-speci c antibodies in murine allogeneic bone marrow transplantation 23 .…”
Section: Introductionmentioning
confidence: 99%